Anti-Inflammatory Effect Of Polyherbal Feed Supplements In Heat Stressed Pigs - M. Lavanya; G.V. Bhaskar Reddy; M. Kamalnath Reddy; N. Sai Anjana; D. Suresh Babu; Bhaskar Ganguly (The Indian Veterinary Journal, 2023)
A study was undertaken to determine the anti-inflammatory effect of poly herbal supplements by measuring the levels of serum high sensitive C - reactive protein (hs-CRP) in the pigs reared during summer months.  Experimental groups supplemented with poly herbal supplements have significantly lower levels of hs-CRP from first to six months of study period when compared to control. The overall mean hs-CRP (mg/dl) levels were reduced from 0.82 to 0.57 during grower phase and 0.82 to 0.46 during finisher phase in control and experimental groups respectively. Based on these results, it can be concluded that addition of poly herbal supplements in feed significantly lower the inflammatory activities in heat stressed pigs.